SISTEM REPOSITORI MENGGUNAKAN ALGORITMA PENCARIAN SEQUENTIAL DAN ANALISIS QOS - Syafikah Kamal; Anwar Anwar; Mursyidah Mursyidah (Sisfo: Jurnal Ilmiah Sistem Informasi, 2018)
Teaching and Learning Process is the concept of combining two concepts,namely teaching and learning conducted by students and lecturers. Thanksto technological developments, there has been a lot of enlargement of theeducation system from the world of conventional face-to-face educationtowards more open education. During this time sharing material files in theteaching-learning process still uses the media manually such as CDs,DVDs, Flashdisks and other physical media. As a result, performance isdisrupted and can slow down the learning process. These weaknesses canbe overcome by utilizing the repository system. This system is a media fordisseminating web-based information. Aiming to build a data repository todetermine storage space capacity by applying data search using theautocomplete feature and sequential algorithm, where the data analyzed isthe quality of the system using the QoS parameters. The system canprovide convenience for students, lecturers or lecturers to share materialfiles quickly and efficiently.